The challenges of corporate entrepreneurship in the disruptive age - Kuratko, Donald F.; Hoskinson, Sherry (Advances in the study of entrepreneurship, innovation, and economic growth (Emerald Publishing Limited), 2019)
Today's age of disruptive technology is a strategic game changer for most organizations. Unpredictable market conditions create unprecedented challenges for simple organizational survival, let alone avenues for innovation and growth. This volume explores this dynamic environment in which corporate entrepreneurship strategies are pursued.